PROSES FORMULASI KEBIJAKAN PENANGGULANGAN KEMISKINAN: Studi kasus Unit Pelaksana Teknis Penanggulangan Kemiskinan Kabupaten Sragen - Irwan Abdu Nugraha (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
All this time poverty reduction policy is partial, it’s so hard to combine all of the perception about poverty reduction because of poverty data is unintegrated, usually data in local government and BPS is different and not synchronous, moreover the poverty services partially will extended the bureaucracy. Sragen create a policy that be a solution to handle poverty problem with established an integrated unit that handle the poverty services like free health services for poor people, scholarship for smart poor student, rebuild the house uninhabitable (RTLH), and usually called by Integrated Services Unit Poverty (UPTPK). In this research, investigator interest to make analysis about how UPTPK can form and who is the actor that most contribute then how is the political intrigues that happened so can formed this UPTPK. The thing that more interested is now all of the policies in Sragen always nuances about poverty reduction. And to answer those questions, using research methods with descriptive approach, that is illustrating the formulation process with analyze data from interviews with relevant parties concerned. Based on research can found some facts, there are from the problem formulation, the issues that developed not only about poverty, but also about bureaucracy in the earlier policies are difficult for the poor people, then the issue policies that appear is caused the campaign from Sragen regent, Agus Faturahman that lift theme about poverty reduction. Society admitted, poverty is a problem that should be solved, but the issue can interested the society when regent campaign. Based on the research there are many factors that influence the policies, and most dominant is economic and political factors. Economic factor are about the budget deficit in the earlier regent leadership that impact the minimum budget to do development policies, so the budget are used for poverty reduction policies. From the policies agenda, there are demand from some group for the regent to realized the promises when his campaign that is Mbelo Wong Cilik. So the demand indirectly is focused to the poverty problem. Furthermore, determination the policies agenda not through DPRD because UPTPK there’s no in SOTK Sragen government, so there’s no discussion about UPTPK legality with DPRD. From the policy determining, UPTPK established just by a regent with the legal basis only a regent decree. Because of UPTPK isn’t in the SOTK Sragen government, as a consequence UPTPK yet manage their own budgeting.Keywords: